The Cause of Shale Oil Overpressure and Its Influence on Productivity in Jimsar Sag - CAO Zhifeng; LIN Jingqi; LING Liang; WANG Xianhu; TAN Xiaobin; WANG Haipeng; ZHAO Hongyi; XU Rui; ZHANG Yanli (Cejing jishu)
Shale oil productivity of Permian Lusaogou formation in Jimsal sag, Junggar basin is positively correlated with formation overpressure strength, but its genetic mechanism is still unclear. Based on geological, well logging and oil testing data, the measured formation pressure of Permian Lucaogou formation in the study area is analyzed, and the genesis mechanism of overpressure is discussed. The effects of overpressure strength on reservoir pore structure, shale oil occurrence state and reservoir productivity are studied by pyrolytic fluorescent flakes, dynamic pore pressure and three-dimensional stress Mohr circle. The results show that hydrocarbon generation supercharging is the main mechanism of formation overpressure. Formation overpressure has a positive effect on the preservation, migration and enrichment of shale oil and the pore structure of the reservoir, which is conducive to the formation of the pressure difference drive of source and reservoir, and the pulse diffusion of oil and gas along micro-fractures to the adjacent sweet spot, which controls the occurrence state, distribution and free oil enrichment of shale oil. The formation and effectiveness of shale oil micro-fractures are controlled by overpressure strength. Micro-fractures make the reservoir "storage holes" and "connecting holes" interconnect with each other, improve the reservoir pore structure, and form a high-quality reservoir with double pore structure of base value holes and fractures. It is conducive to the formation of high oil saturation and free oil saturation, and enhance the seepage capacity of shale oil. At present, the region with the highest production capacity is evenly distributed in the overlap of the hydrocarbon generating center and the overpressure center. Therefore, high free oil saturation, fracture development degree and effectiveness caused by overpressure strength are the main internal factors affecting shale oil productivity. The research results provide a basis for prediction and efficient development of shale oil favorable area of Permian Lusaogou formation in Jimsar sag.